PREREQUISITES FOR ENTRY OF VOCATIONAL EDUCATION INTO THE SYSTEM OF PUBLIC-PRIVATE PARTNERSHIP IN UKRAINE (Innovative professional education, 2022)
The introduction of public-private partnership is one of the links in education reform, a mechanism for active integration of the system of professional (vocational) education in the social structure of communities and bringing education closer to world standards. Vocational education should be seen as a chain of interaction between private business, the state and educational institutions. The effect of the introduction of public-private partnership in the field of professional (vocational) education will be not only to save the total budget, but also to increase the efficiency of the education system.
Keywords: vocational education; public-private partnership; social structure of communities; education applicant; educational institution